Relating rock microstructure to flow paths and chemical reactions: application to CO2 injection in carbonates - Vialle, Stephanie; Dvorkin, J.; Mavko, G. (EAGE, 2013)
This study is about heterogeneities of carbonate rocks with respect to their pore-size distribution obtained by Mercury Intrusion Capillary Pressure (MICP) tests, and the implication of these heterogeneities for the geochemical evolution of a reactive fluid/rock system (e.g., CO2-rich fluid/carbonate). We found that the studied rocks show heterogeneities at a scale much smaller than the typical volume of a MICP test (1/5 of a 2.5 cm core plug). We thus subdivided the rock pore system into microstructural facies based on their pore throat sizes (e.g. tight micrite, small vugs, microporous rounded micrite...), got a characteristic value of their petrophysical properties (porosity, effective surface area and permeability) from the MICP data and rock physics relationships, and provide a new form of the Péclet and Damkhöler numbers, expressed as a function of the aforementioned permeability and effective surface area. These numbers allowed us to infer the dominant process (i.e., diffusion, advection or kinetics) controlling the dissolution/precipitation reactions induced by the CO2-rich fluid. Because of heterogeneities in the pore microstructure, we found that different processes were locally dominant, which rendered some zones (e.g., microporous rounded micrite) chemically more reactive than others (e.g., tight micrite or spar cement).